IMPLEMENTATION OF THE COLLABORATIVE PROBLEM SOLVING (CPS) LEARNING MODEL IN MATHEMATICS INSTRUCTION ON THE TOPIC OF SYSTEMS OF TWO-VARIABLE LINEAR EQUATIONS (SPLDV) - Dosniroha, Devitha; Sulistyaningsih, Murni; Tilaar, Anetha L.F. (Jurnal Pendidikan Matematika dan IPA, 2026)
This study aims to identify whether the average learning outcomes of students who learn using the Collaborative Problem-Solving learning model are higher than the average learning outcomes of students who learn using the Direct learning model (lecture method) on the Two-Variable Linear Equation System material. This study uses a posttest-only control group design. The population of this study was all eighth-grade students and the sample in this study was class VIII-A as an experimental class consisting of 20 students and class VIII-B as a control class consisting of 10 students at SMP Negeri 3 Tondano in the even semester of the 2024/2025 academic year. The results revealed that there was a difference in the average learning outcomes of students taught using the Collaborative Problem-Solving learning model with students taught using the Direct learning model. Based on the above results, it can be concluded that using the Problem-Based Learning model can improve students' mathematics learning outcomes in the topic of Two-Variable Linear Equation Systems.